(untitled) (ModaPalavra e-periódico, 2009)
This article reveals how the man transforms himself in a social being by the appropriation of appearance symbols and why they can be used as tools for analysing the society as a whole, just as the social transformations can be used to analyse the appearance manifestation. Parting from observations on clothing from the novel Orlando, by Virginia Woolf, the relation between appearance and communication, explained from its beginning, is developed enhanced by literature, sociological and anthropological studies. The myth of the pure functionality of clothing is broken to make clear the importance of dress codes in social life and in the construction of the individual, as well as its role inside culture.